2021
DOI: 10.1093/ofid/ofab283
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on UNAIDS 90–90–90 Targets: Calls for New HIV Care Models

Abstract: We compared 90-90-90 targets in 2020, during the COVID-19 pandemic, with the targets across the period 2017-2019 in people living with HIV. We observed a significant loss in the 90-90-90 objectives in 2020 when compared to 2017-2019 that might be attributable to COVID-19 crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…An 85% reduction in HIV/gonorrhea/chlamydia tests was reported in the first quarter of the year 2020 in the Boston area. The same reduction was reported in Lombardy, Italy (7). A report from Melbourne showed that 25% of PrEP users stopped taking PrEP during the COVID-19 outbreak (16) (Table 1).…”
Section: % Use Combination Preventionsupporting
confidence: 68%
See 1 more Smart Citation
“…An 85% reduction in HIV/gonorrhea/chlamydia tests was reported in the first quarter of the year 2020 in the Boston area. The same reduction was reported in Lombardy, Italy (7). A report from Melbourne showed that 25% of PrEP users stopped taking PrEP during the COVID-19 outbreak (16) (Table 1).…”
Section: % Use Combination Preventionsupporting
confidence: 68%
“…Between April and June 2020 alone, the COVID-19 has led to about a 30% reduction in the use of HIV testing services in communities and health facilities in Uganda (6). Compared to the pre-COVID-19 period, there was about 20% reduction of HIV tests in Italy (7). In addition, since more than half of HIV clinics had stopped in-person visits and blood testing and focused on ART drug distribution to patients diagnosed before the pandemic (8), the second "95%" target of ART might be the least impacted.…”
mentioning
confidence: 99%
“…HIV health systems were overloaded and in 42.1% of cases, HIV drug procurement might have been affected [8]. Additionally, Western Europe reported that there were significant losses in the 90-90-90 objectives in 2020, which were associated with the introduction of lockdowns and limited access to HIV outpatient services [1]. This situation, worldwide, led to new ideas and solutions that allowed the continuity of care for HIV patients to be maintained during this difficult time for the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has been a challenging time for all medical services, especially at the beginning of the pandemic, and it has been difficult to maintain continued care for HIV patients [1]. After almost two years, it is still a challenge, but it is also an opportunity for Central and Eastern Europe (CEE) to modernize old systems and introduce modern tools to HIV care [2].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of SARS-CoV-2 epidemics may have also affected established measures for the prevention and diagnosis of HIV infection and other sexually transmitted diseases and the clinical care of HIV-infected patients, although data are limited [7,8]. The WHO warned that the access to HIV medicines could be severely impacted by COVID-19 [9].…”
Section: Introductionmentioning
confidence: 99%